2019
DOI: 10.3389/feart.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes of Seismic Velocity Caused by Volcanic Activity at Mt. Etna Revealed by the Autocorrelation of Ambient Seismic Noise

Abstract: On active volcanoes, ambient noise-based seismic interferometry can be a very useful monitoring tool as it allows to detect very slight variations in seismic velocity associated with magma transported toward the surface. However, the classical cross-station approach occasionally fails to detect seismic velocity changes related to eruptive activity, even on very active, well-instrumented volcanoes such as Mt. Etna. In this work, we explored an improved ambient noise-based monitoring strategy by performing the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This phase was specifically associated with the deep recharge of the reservoir at 7-12 km b.s.l. as evidenced by a progressive increase of CO 2 flux (Figure 2d), of the CO 2 / SO 2 ratio and of 3 He/ 4 He ratios (Gurrieri et al, 2021;Paonita et al, 2021) in agreement with the pressure source estimated by deformation (Cannavo' et al, 2019). The seismicity in the corresponding period is scattered down to 30 km of depth (Figure 1c; Alparone et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This phase was specifically associated with the deep recharge of the reservoir at 7-12 km b.s.l. as evidenced by a progressive increase of CO 2 flux (Figure 2d), of the CO 2 / SO 2 ratio and of 3 He/ 4 He ratios (Gurrieri et al, 2021;Paonita et al, 2021) in agreement with the pressure source estimated by deformation (Cannavo' et al, 2019). The seismicity in the corresponding period is scattered down to 30 km of depth (Figure 1c; Alparone et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…De Plaen et al. (2019) suggested that seismic velocity decreases result from intense pressurization of magma within the plumbing system for 2013–2014 paroxysmal eruptions. Patanè et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies linked volcanic inflation to dv / v decreases rather than increases (e.g., Brenguier et al., 2011; Brenguier et al., 2016; De Plaen et al., 2016, 2019; Machacca‐Puma et al., 2019; Takano et al., 2017). However, local velocity increases could occur if a shallow magma, gas, or hydrothermal reservoir, as it may exist beneath Bezymianny (Ivanov et al., 2016; Koulakov et al., 2017, 2021), inflates and, thereby, causes local compaction through increased pressure (Caudron et al., 2021, 2022; Donaldson et al., 2017, 2019; Hotovec‐Ellis et al., 2015; Yates et al., 2019).…”
Section: Discussion Of Physical Mechanisms Causing Velocity Changesmentioning
confidence: 99%
“…Sens‐Schönfelder and Wegler (2006) overcame this limitation by computing dv / v from ambient seismic noise using a technique called passive image interferometry (PII). Along with other factors, such as hydrological fluctuations (Clements & Denolle, 2018; Illien et al., 2021; Mao et al., 2022; Rodríguez Tribaldos & Ajo‐Franklin, 2021), seasonal variations due to meteorological changes (Hillers et al., 2015; Sens‐Schönfelder & Wegler, 2006; Wang et al., 2017), freezing‐thawing cycles (Gassenmeier et al., 2014; James et al., 2019; Lindner et al., 2021; Steinmann et al., 2021), and earthquake‐induced subsurface damages (Bonilla et al., 2019; Boschelli et al., 2021; Brenguier, Campillo, et al., 2008; Hobiger et al., 2016; Viens et al., 2018; Wegler et al., 2009; Wegler & Sens‐Schönfelder, 2007), velocity changes due to volcanic inflation cycles have been detected by PII (Bennington et al., 2015; Brenguier, Shapiro, et al., 2008; De Plaen et al., 2016, 2019; Donaldson et al., 2017, 2019; Hirose et al., 2017; Machacca‐Puma et al., 2019; Obermann, Planès, Larose, & Campillo, 2013; Olivier et al., 2019; Ruiz et al., 2022; Sens‐Schönfelder et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The autocorrelation function (ACF), a form of seismic interferometry, is considered an approximation of the zero-offset reflection seismogram beneath a site (Claerbout 1968). Since it only requires a single station, ACF provides an efficient tool for imaging and monitoring temporal changes of seismic properties below the surface (Richter et al 2014, Bonilla et al 2019, De Plaen et al 2019, Kim & Lekic 2019, Lu & Ben-Zion 2022, especially when a limited number of seismic stations are available. These studies shed light on properties and susceptibility of subsurface materials to failure, which are of great importance to interpreting observed seismic motion, reliability of underground facilities, and other applications.…”
Section: Introductionmentioning
confidence: 99%